PWE-347 Adherent, invasive mucosa-associated e. coli isolates from colorectal cancer patients activate WNT signalling. (22nd June 2015) - Meehan, B; Campbell, B; Rhodes, J
Abstract : Introduction: Increased numbers of adherent, invasive E.coli (AIEC) have been reported on and within intestinal epithelial cells of patients with colorectal cancer (CRC). 1 Cancer-inducing activity of AIEC have recently been described by our group and others, including potential for genotoxicity and promotion of angiogenesis. 2, 3, 4 We hypothesise that CRC-associated AIEC may also trigger key cancer signalling pathways that support development and progression of early carcinogenesis, including (Wingless) Wnt/b-catenin cell signalling pathway. 5 Method: Two human CRC cell-lines SW-480 and DLD1 were infected with CRC mucosa-associated AIEC isolates HM44 and HM358 1 for 4h at multiplicity of infection of 10. RNA was isolated, and synthesised cDNA subjected to RT 2 PCR Wnt Target Array (84 Wnt-relevant genes). Gene expression changes were confirmed by Roche Lightcycler qPCR and protein expression by immunoblot (0.5h to 4h infections). Results: In response to 4h infection with CRC-associated AIEC isolates HM44 and HM358, 11 Wnt target-genes were significantly up-regulated and 7 significantly down-regulated, many regulating cell cycle, cell proliferation, migration and angiogenesis. Key genes up-regulated in SW480 cells included cyclooxygenase-2 ( PTGS-2/COX2 ), increased 8.1 ± 0.9 and 9.2 ± 1.0 fold (both P = 0.0002), Fos-related antigen 1 ( FOSL1 ) increased 6.1 ± 0.6 and 7.9 ± 1.9 fold (P < 0.01), and vascular endothelial growth factor-A ( VEGFA ) upregulated 4.6 ± 0.3 and 4.2 ± 0.2 fold respectively (P < 0.0001). Down-regulated genes (>2 fold change) included a known CRC tumour suppressor, Wnt-1 inducible signalling pathway 2 ( WISP2 ); P < 0.05. Similar gene changes were seen using DLD-1 cells, and confirmed by qPCR. AIEC also significantly increased cellular protein levels; e.g. COX2, up 5.7 ± 0.7 and 2.8 ± 0.04 fold respectively (both P < 0.01; N=3, n = 3). In addition, b-catenin increases were 2–3 fold at 2h and 4h post-infection (P < 0.05). Conclusion: Early indications suggest a key contribution of cancer-promoting activity of CRC-mucosa-associated E.coli events may be through ability to activate the Wnt signalling pathway. Confirmation of the importance of these findings is being investigated in vivo using a mono-association mouse model, 2 along with a CRC E.coli fosmid-library screening approach 3 to identify specific bacterial factors triggering these early cancer-promoting signals. Disclosure of interest: B. Meehan: None Declared, B. Campbell Conflict with: Received honoraria from Amgen and Falk., J. Rhodes Conflict with: Is/has been a member of advisory boards for Atlantic, Procter and Gamble and Falk, has received honoraria from Abbott, Falk, Ferring, Glaxo Smith Kline, Procter and Gamble and Schering Plough. References: Martin, et al . Gastroenterology 2004;127:80–93 Arthur JC, et al . Science 2012;338:120–23 Prorok-Hamon M, et al . Gut 2014;63:761–70 Buc, et al . PLoS One 2013;8(2):e56964 Schneikert J, Behrens J. Gut 2007;56:417–25